Household Vulnerability and Migration Decisions under Food Insecurity in Nangarhar, Afghanistan: Kerentanan Rumah Tangga dan Keputusan Migrasi di Bawah Kondisi Ketahanan Pangan yang Buruk di Nangarhar, Afghanistan - Imranullah Akhtar; Ahmad Shah Qaderi; Muhammad Ibrahim Sekandary (SiRad: Pelita Wawasan, 2026)
In a country like Afghanistan, whose economy is largely based on agriculture, food security and migration are deeply intertwined, especially in Nangarhar province. This study assesses the relationship between household food security, economic status, and migration and attempts to clarify the role of food insecurity in shaping migration decisions. The study was conducted based on a cross-sectional survey, in which data were collected from 520 farmers from 9 districts of Nangarhar province. A structured questionnaire was used to collect data, and purposive sampling was used. Household food consumption was assessed based on the previous seven days, as well as children’s school attendance and household economic status. Descriptive statistics and Pearson Correlation were used to analyse the data to obtain accurate and reliable results. The results of the study show that although most households have access to basic foods such as bread and rice every day, they consume very little of nutritious foods such as meat, dairy products, and vegetables. In addition, children’s school dropout is closely linked to the poor economic status of households. The findings indicate that malnutrition and economic problems are important drivers of migration. The study concludes that strengthening targeted programs for household economic empowerment, agricultural development, and food security can reduce malnutrition and mitigate the negative impacts of livelihood-based migration. This study provides important scientific and practical insights for development policy and migration management in Afghanistan. [Di negara seperti Afghanistan, yang ekonominya sebagian besar berbasis pada pertanian, ketahanan pangan dan migrasi saling terkait erat, khususnya di provinsi Nangarhar. Studi ini menilai hubungan antara ketahanan pangan rumah tangga, status ekonomi, dan migrasi, serta berupaya mengklarifikasi peran ketidaktahanan pangan dalam membentuk keputusan migrasi. Penelitian ini dilakukan berdasarkan survei potong-lintang (cross-sectional), di mana data dikumpulkan dari 520 petani dari 9 distrik di provinsi Nangarhar. Kuesioner terstruktur digunakan untuk mengumpulkan data, dan teknik pengambilan sampel bertujuan (purposive sampling) diterapkan. Konsumsi pangan rumah tangga dinilai berdasarkan tujuh hari sebelumnya, serta kehadiran anak-anak di sekolah dan status ekonomi rumah tangga. Statistik deskriptif dan Korelasi Pearson digunakan untuk menganalisis data guna mendapatkan hasil yang akurat dan andal. Hasil studi menunjukkan bahwa meskipun sebagian besar rumah tangga memiliki akses ke makanan pokok seperti roti dan nasi setiap hari, mereka mengonsumsi sangat sedikit makanan bergizi seperti daging, produk susu, dan sayuran. Selain itu, angka putus sekolah anak-anak berkaitan erat dengan status ekonomi rumah tangga yang buruk. Temuan ini menunjukkan bahwa malnutrisi dan masalah ekonomi merupakan pendorong utama migrasi. Studi ini menyimpulkan bahwa penguatan program-program yang ditargetkan untuk pemberdayaan ekonomi rumah tangga, pengembangan pertanian, dan ketahanan pangan dapat mengurangi malnutrisi serta memitigasi dampak negatif dari migrasi berbasis penghidupan. Studi ini memberikan wawasan ilmiah dan praktis yang penting bagi kebijakan pembangunan dan pengelolaan migrasi di Afghanistan.]